Synthesis and characterization of Fex Si(1-x) O2 anode nanomaterial for lithium-ion batteries - Garrido, Catherine P.; Cervera, Rinlee Butch M. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Silicon-based materials have been tapped as promising anodes for lithium ion batteries due to the high theoretical specific capacity of about 4200 mAhg-1. However, the challenge in using such high capacity anode material is the large volumetric change during lithiation and delithiation causing capacity fading. In this study, in order to address the large volumetric change associated with silicon, amorphous nanograin-sized SiO2 incorporated with Fe having compositions of FexSi1-xO2 (x=0.05, 0.10) have been synthesized using a modified sol-gel process and characterized for its thermal, structural, morphological, and electrochemical properties. From the different characterization results, the study was successful in synthesizing nanograin-sized Fe-doped amorphous silica as supported by XRD, TEM, SEM, and EDS analysis. The samples synthesized at 400°C and 600°C suggest completely amorphous SiO2 structures, with the latter showing peaks attributed to low-crystallinity -Fe2O3. The samples synthesized at 800°C suggest a combination of crystalline and amorphous SiO2 with an accompanying grain growth. From the electrochemical testing results using galvanostatic charge-discharge, the sample synthesized at 800°C with x=0.10 yielded the highest lithiation capacity of 1493.54 mAhg-1, which is 83.94% of the theoretical capacity of SiO2 and 4 times higher than that of the commercial graphitic anode material; and 1822.99 mAhg-1 delithiation capacity. The possible large contact area between the active material and the current collector and the incorporation of higher F3 content enhance the electrochemical performance of the 800°C annealed x=0.10 Fe-doped SiO2 sam
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Lithium ion batter; Lithium ce; Ano